(untitled) (Journal of the College of Basic Education, 2022)
(60) swabs of bedsore infections were collected from lying patients. Peptostreptococcus anaerobius was isolated by (34.7%) of these infections, in addition to isolating other aerobic and anaerobic bacteria, including Escherichia coli, Pseudomonas aeruginosa, and Bacteroides fragilis. The aerobic bacterial species showed Anaerobes showed a clear variation in their sensitivity to antibiotics, so the antibiotics Metronidazole, Ciprofloxacin, and Augmentin were the best antibiotics for the treatment of bedsores, as the sensitivity of the isolates ranged between (66.6%) to (100%). The results of the investigation of the virulence factors of P.anaerobius confirmed that the bacterial isolates showed a positive result for the production of hemolasin, beta-lactamase, lipase, protease and biofilm production at a rate of (100%, 100%, 64.7%, 70.5%, 100%). Straight .